# At Cheng's Bike Rentals, it costs \$25 to rent a bike for 5 hours. How many dollars does it cost per hour of bike use?

crystaldewar55C   ·   06.06.2022 14:00
28.06.2019 15:50

28.06.2019 15:30

g(x) = 3*(8(3^(x−2))+2)

g(x) = 24 (3^(x-2) )+6

the factor is 2

step-by-step explanation:

let f(x)=8(3^(x−2)+2)

to stretch a graph by 3, it would be 3f(x)

g(x) =3f(x)

g(x) = 3*(8(3^(x−2))+2)

g(x) = 24 (3^(x-2) )+6

x     −2     0     2     4     6

f(x) 1/64 1/16   1/4     1     4

1/64 * z * z = 1/16

i multiplies by z twice because it its 2 steps from -2 to 0

1/64 z^2 = 1/16

multiply by 64 to clear the fraction on the left side

1/4 * 64 z^2 =1/16 *64

z^2 = 4

take the square root of each side

sqrt(z^2) = ±sqrt(4)

z = ±2

we are multiplying by 2 each time.

24.06.2019 21:30

(2 x^3 + 7 x^2 + 5 x + 2)/(x (x + 2))

step-by-step explanation:

simplify the following:

x/x^2 + 3 x + 2 - (x (x + 1))/(x + 2)

combine powers. x/x^2 = x^(1 - 2):

x^(1 - 2) + 3 x + 2 - (x (x + 1))/(x + 2)

1 - 2 = -1:

x^(-1) + 3 x + 2 - (x (x + 1))/(x + 2)

put each term in 1/x + 3 x + 2 - (x (x + 1))/(x + 2) over the common denominator x (x + 2): 1/x + 3 x + 2 - (x (x + 1))/(x + 2) = (x + 2)/(x (x + 2)) + (3 x^2 (x + 2))/(x (x + 2)) + (2 x (x + 2))/(x (x + 2)) - (x^2 (x + 1))/(x (x + 2)):

(x + 2)/(x (x + 2)) + (3 x^2 (x + 2))/(x (x + 2)) + (2 x (x + 2))/(x (x + 2)) - (x^2 (x + 1))/(x (x + 2))

(x + 2)/(x (x + 2)) + (3 x^2 (x + 2))/(x (x + 2)) + (2 x (x + 2))/(x (x + 2)) - (x^2 (x + 1))/(x (x + 2)) = ((x + 2) + 3 x^2 (x + 2) + 2 x (x + 2) - x^2 (x + 1))/(x (x + 2)):

(2 + x + 3 x^2 (x + 2) + 2 x (x + 2) - x^2 (x + 1))/(x (x + 2))

3 x^2 (x + 2) = 3 x^3 + 6 x^2:

(2 + x + 3 x^3 + 6 x^2 + 2 x (x + 2) - x^2 (x + 1))/(x (x + 2))

2 x (x + 2) = 2 x^2 + 4 x:

(2 + x + 6 x^2 + 3 x^3 + 2 x^2 + 4 x - x^2 (x + 1))/(x (x + 2))

-x^2 (x + 1) = -x^2 - x^3:

(-x^2 - x^3 + 3 x^3 + 6 x^2 + 2 x^2 + 4 x + x + 2)/(x (x + 2))

grouping like terms, 3 x^3 - x^3 + 6 x^2 + 2 x^2 - x^2 + 4 x + x + 2 = (3 x^3 - x^3) + (6 x^2 + 2 x^2 - x^2) + (x + 4 x) + 2:

((3 x^3 - x^3) + (6 x^2 + 2 x^2 - x^2) + (x + 4 x) + 2)/(x (x + 2))

3 x^3 - x^3 = 2 x^3:

(2 x^3 + (6 x^2 + 2 x^2 - x^2) + (x + 4 x) + 2)/(x (x + 2))

6 x^2 + 2 x^2 - x^2 = 7 x^2:

(2 x^3 + 7 x^2 + (x + 4 x) + 2)/(x (x + 2))

x + 4 x = 5 x:

answer:   (2 x^3 + 7 x^2 + 5 x + 2)/(x (x + 2))

06.06.2022 14:00

25÷5=5  ### Other questions on the subject: Mathematics

What is this inequality notation? t is less then or equal to 2...
Mathematics
21.06.2019 15:30
Of the ones listed here, the factor that had the greatest impact on the eventual destruction of native americans' ways of life was the development of the a) automobile. b) highway...
Mathematics
21.06.2019 17:00
Is appreciated! graph the functions and approximate an x-value in which the exponential function surpasses the polynomial function. f(x) = 4^xg(x) = 4x^2options: x = -1x = 0x = 1x...
Mathematics
21.06.2019 17:30
Alana has 12.5 cups of flour with which she is baking four loaves of raisin bread and one large pretzel. the pretzel requires 2.5 cups of flour to make. how much flour is in each l...
Mathematics
21.06.2019 18:10
What is the absolute value of the complex number -4-sqrt2i...
Mathematics
21.06.2019 19:10
In the geometric progression –3, 12, −48… what term is 3,072?...
Mathematics
21.06.2019 19:30
Ineed with this problem 21 show steps ...
Mathematics
21.06.2019 19:30
Someone me! if you’re smart you can solve this! ...
Mathematics
21.06.2019 20:00
Eliza wants to make \$10,000 from her investments. she finds an investment account that earns 4.5% interest. she decides to deposit \$2,500 into an account. how much money will be in...
Mathematics
21.06.2019 21:00